Immunosuppressive enzymes in the tumor microenvironment - Valérie Molinier‐Frenkel; Flavia Castellano (2017)
Antigen encounter by T lymphocytes induces important metabolic changes. Antitumor T lymphocytes enter in a metabolic competition with tumors, which divert feedback mechanisms of the immune response. Immunosuppressive enzymes, modifying the nutrient availability and leading to the production of toxic catabolites, represent one of these mechanisms, contributing to the metabolic halo in which T lymphocytes evolve during immune responses. Two classes of immunosuppressive enzymes, expressed by the tumor cells or by cells of the microenvironment, have been described: those catabolizing essential or semiessential amino acids, tryptophan, arginine, and phenylalanine and the ectoenzymes, which degrade the ATP to produce adenosine. These enzymes are described, as well as some of the ongoing clinical trials aiming to block them in cancer treatment.